Experimental determination of lateral sway of a pneumatic spring when passing through a railroad switch in conditions of provision of high-speed trains` safety - Andrii Kuzyshyn; Vitalii Kovalchuk; Yulia Sobolevska; Julia Lesiv (Transport Technologies)
The operation of railway rolling stock under high-speed conditions is crucial for Ukraine, as it will increase the throughput and carrying capacity of the railway network and improve the mobility of people in large cities. The dynamic behavior of the pneumatic spring, as the main structural element of the suspension system of high-speed rolling stock, has been studied. It is noted that the issue of the dynamic performance of the pneumatic spring is of broad scientific interest, as it directly affects the dynamic indicators and safety of the rolling stock when interacting with the track. Since the force interaction is random, depending on the condition of the rolling stock and the track, the study is based on experimental research on the dynamic behavior of the pneumatic spring. A methodology for the experimental determination of the lateral sway of the pneumatic spring of high-speed rolling stock when moving through a rail switch has been developed. It included testing the movement of a test stand over the switch and crossing in both forward and reverse directions. The vertical deformations of the pneumatic spring were recorded at diametrically opposite points in the longitudinal direction. It was found that the deformation of the pneumatic spring causes a tilt angle of the spring, with the average values being 0.667 degrees for forward movement, 0.697 degrees for the reverse for the switch blade area, and 0.369 degrees for forward movement, 0.468 degrees for the reverse for the crossing area. The results obtained can be used in the study of the dynamic characteristics of the pneumatic spring, allowing for the evaluation of its dynamic and safety indicators even at the design stage of rolling stock. In addition, the results will enable monitoring of the technical condition of the pneumatic spring, ensuring key safety indicators in high-speed operation.